Identification of a Mycobacterium bovis BCG Auxotrophic Mutant That Protects Guinea Pigs against M. bovis and Hematogenous Spread of Mycobacterium tuberculosis without Sensitization to Tuberculin - Chambers, Mark A. (American Society for Microbiology, 2000)
Tuberculosis remains one of the most significant diseases of humans and animals. The only currently available vaccine against this disease is a live, attenuated vaccine, bacillus Calmette-Guérin (BCG), which was originally derived from Mycobacterium bovis and despite its variable efficacy is the most widely administered vaccine in the world. With the advent of the human immunodeficiency virus-AIDS pandemic concern has been raised over the safety of BCG. Moreover, since BCG sensitizes vaccinated individuals to the tuberculin test, vaccination with BCG prevents diagnosis of infection in vaccinated individuals. Recently, auxotrophic strains of BCG have been generated by insertional mutagenesis which have been shown to be safer than the parent BCG strain following administration to mice with severe combined immunodeficiency disease. These strains have also been shown to give comparable protection against intravenous and intratracheal challenge of BALB/c mice with M. tuberculosis relative to conventional BCG. Here we report that one of these mutants, a leucine auxotroph of BCG, conferred significant protection of the lungs and spleens of guinea pigs infected with M. bovis and protection of the spleens of guinea pigs infected with M. tuberculosis in the absence of a cutaneous hypersensitivity reaction to tuberculin. Therefore, protective immunity to tuberculosis may, at least in part, be achieved without sensitization to the tuberculin skin test. These results indicate that it may be possible to develop a new generation of vaccines based on BCG that are protective, are safe for use in the immunocompromised, and do not preclude the use of the tuberculin skin test in both humans and animals.